High‐precision U‐Pb geochronology of the Jurassic Yanliao Biota from Jianchang (western Liaoning Province, China): Age constraints on the rise of feathered dinosaurs and eutherian mammals. (22nd October 2016) - Chu, Zhuyin; He, Huaiyu; Ramezani, Jahandar; Bowring, Samuel A.; Hu, Dongyu; Zhang, Lijun; Zheng, Shaolin; Wang, Xiaolin; Zhou, Zhonghe; Deng, Chenglong; Guo, Jinghui
Abstract: The Yanliao Biota of northeastern China comprises the oldest feathered dinosaurs, transitional pterosaurs, as well as the earliest eutherian mammals, multituberculate mammals, and new euharamiyidan species that are key elements of the Mesozoic biotic record. Recent discovery of the Yanliao Biota in the Daxishan section near the town of Linglongta, Jianchang County in western Liaoning Province have greatly enhanced our knowledge of the transition from dinosaurs to birds, primitive to derived pterosaurs, and the early evolution of mammals. Nevertheless, fundamental questions regarding the correlation of fossil‐bearing strata, rates of dinosaur and mammalian evolution, and their relationship to environmental change in deep time remain unresolved due to the paucity of precise and accurate temporal constraints. These limitations underscore the importance of placing the rich fossil record of Jianchang within a high‐resolution chronostratigraphic framework that has thus far been hampered by the relatively low precision of in situ radioisotopic dating techniques. Here we present high‐precision U‐Pb zircon geochronology by the chemical abrasion isotope dilution thermal ionization mass spectrometry (CA‐ID‐TIMS) from three interstratified ash beds previously dated by secondary‐ion mass spectrometry (SIMS) technique. The results constrain the key fossil horizons of the Daxishan section to an interval spanning 160.89 to 160.25 Ma with 2σ analytical uncertainties that range from ±46 to ±69 kyr. These data place the Yanliao Biota from Jianchang in the Oxfordian Stage of the Late Jurassic, and mark the Daxishan section as the site of Earth's oldest precisely dated feathered dinosaurs and eutherian mammals. Key Points: New CA‐ID‐TIMS U‐Pb geochronology for the fossil‐rich Jurassic terrestrial strata in northeastern China with precision of ±45 to 70 kyr Lanqi Formation in Jianchang of western Liaoning Province was deposited between ca. 160.89 and 160.25 Ma in less than 717 kyr Oldest documented feathered dinosaurs and eutherian mammals belonging to Yanliao Biota appeared in northeastern China in Oxfordian